KUALITAS PELAYANAN PRAMUWISATA DI OBJEK WISATA DANAU BUATAN RUMBAI PESISIR KOTA PEKANBARU - Salsabila Putri Suhendra; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT Pekanbaru has the opportunity to become a leading destination that can be further developed, because since 2019 and 2022 tourists have continued to increase coming to the city of Pekanbaru. There are also many tourist objects in the city of Pekanbaru, one of which is in the Rumbai sub-district, the Rumbai Coastal Artificial Lake Tourism Object in Pekanbaru City. This study aims to determine the Quality of Tour Guide Services at the Rumbai Coastal Artificial Lake Tourism Object in Pekanbaru City, based on the research that has been done, this research uses a qualitative method. The subject of this research is the Tourism Object of the Coastal Rumbai Artificial Lake in Pekanbaru City. Data collection was carried out by means of documentation studies, observations, interviews, questionnaires and documents. The results showed that the quality of the Artificial Lake Rumbai Coastal Tourism Object in Pekanbaru City is 4, namely: Assurance, Responsiveness, Reliability and Empathy owned by the Artificial Lake Tourism Object are in a pretty good category. Keywords: Quality of Tour Guide Service, Artificial Lake TourismAbstract